THE EFFECT OF WORK MOTIVATION AND WORK DISCIPLINE ON EMPLOYEE PERFORMANCE AT THE LIBRARY AND ARCHIVES SERVICE KABUPATEN BUOL: PENGARUH MOTIVASI KERJA DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN DI LAYANAN PERPUSTAKAAN DAN ARSIP KABUPATEN BUOL - Safitri S. Hilala; Hedrat M. Nure (International Journal of Economic Entrepreneurship and Business Management, 2025)
This study aims to find out and analyze the influence of work motivation and work discipline on employee performance at the Buol Regency Library and Archives Office. This study uses a type of quantitative research. The source of data is in the form of primary data, which is data obtained by conducting research directly related to this research. The population in this study is all ASN employees at the Buol Regency Library and Archives Service which totals 32 people and the sample used by the entire population is 32 respondents. The data analysis techniques used were classical assumption tests, multiple linear regression and hypothesis testing. The results of this study show that work motivation partially affects Employee Performance, Work discipline partially affects Employee Performance, work motivation and work discipline simultaneously affect Employee Performance.From the two variables studied, work motivation and work discipline based on respondents' responses showed a good level of assessment, this was followed by the percentage of responses given by respondents from the questionnaire.